Bolton Ratio of Different Angle’s Classifications in a School Children Sample of Erbil City: A Cross‑sectional Study - Amanj R. Ibrahim; Zana Q. Omer; Hasan S. Hasan; Walaa M. Saleem AlMola (Polytechnic Journal)
Aims of this study were to determine both the Bolton anterior and overall ratios in a representative sample of Erbil schoolchildren of Normal occlusion and Cl I, Cl II div I, div II, and Cl III malocclusion, also to find if there are any gender differences. Numerical data were obtained, comprised of 320 samples study casts of students with a mean age of 13–15 years selected from different schools in Erbil City. The casts were divided into 5 groups according to the type of malocclusion: Normal (n = 64), Cl I (n = 64), Class II div I (n = 64), Class II div II (n = 64), and Class III subjects (n = 64). The measurement of the greatest mesiodistal width of the teeth was performed using digital Vernier directly on the study casts, from the distal surface of the left first molar to the distal surface of the right first molar. The overall and anterior ratios between the maxillary and mandibular teeth were computed and evaluated using Bolton’s method. The results revealed that the mean anterior ratio (78.863) was higher and statistically significantly different from anterior Bolton’s (77.2) and also the mean overall ratio was not statistically significant different from Bolton’s ratio (91.3) (P = 0.239), with respect to the overall and anterior ratios among all the groups, statistically significant differences were found. Differences between genders were analyzed using a t-test. The results showed that there were no significant differences between males and females. There were non-significant differences between the findings of the present study and those of Bolton’s study for overall ratio and anterior ratio, but among all five classifications, there was a significant difference of Erbil population not similar to Bolton ratio and there was no significant difference between males and females.